Antioxidative effect of Periplaneta americana extract on dextran sulfate sodium-induced ulcerative colitis through activation of the Nrf2 signal - Jianzhong Wu; Zhen Zhang; Qimei Wu; Linli Zhang; Zhipeng Chen; Hairong Zhao; Xiumei Wu; Yu Zhao; Chenggui Zhang; Jian Ge; Heng Liu (Taylor & Francis Group, 2023)
AbstractContext Periplaneta americana L. (Blattariae) is used as a treatment for ulcerative colitis (UC) in Chinese traditional medicine.Objective To evaluate the antioxidative activity of P. americana whole body ethanol extract (PAE) on UC mice and whether glycine and proline could be used for quality control and identification of active PAE components.Materials and methods NCM460 cells were pre-incubated in PAE, AA-L, AA-M, and AA-H (low, high and medium doses of proline and glycine), then treated with recombinant human TNF-α. The glutathione (GSH), malondialdehyde (MDA), superoxide dismutase (SOD) and reactive oxygen (ROS) levels were determined. UC mice were fed with water containing 2.5% dextran sulfate sodium (w/v) after pre-treatment with different doses of PAE once a day for 7 days. ELISA was used to detect the concentrations of inflammation-related factors. Colon tissues of mice were used to detect the activity of myeloperoxidase (MPO), GSH, MDA, and SOD. Histological changes were observed using H&E staining. The expression of target proteins was determined by western blotting.Results In vivo, PAE treatment reduced the DAI score more than in the model group, restoring the weight and colonic length. It also reduced the severity of colitis, and inflammatory and oxidative stress intensity. Additionally, western blotting showed that the Nrf2 pathway was activated by PAE. In vitro PAE significantly alleviated TNF-α-induced cell damage and oxidative stress, which is relevant to the activation of the Nrf2 pathway.Conclusions PAE may relieve oxidative stress through the Nrf2 signaling pathway, and proline and glycine may be used as active components of its antioxidative stress activity.